Hypomontagnella (Hypoxylaceae): A new genus segregated from Hypoxylon by a polyphasic taxonomic approach - Lambert, Christopher (2018)
During a survey of xylarialean Sordariomycetes in North-western Argentina, several collections representing a new species morphologically resembling the pantropical Hypoxylon monticulosum was encountered. They were studied by a combination of morphological and chemotaxonomic studies along with a multi-locus phylogeny of Hypoxylon and related genera of the Hypoxylaceae based on a combined ITS, LSU, TUB2, and RBP2 dataset. The phylogenetic tree revealed that DNA sequences of the new fungus clustered together with Hypoxylon monticulosum and Hypoxylon submonticulosum in a separate clade. In addition, all representatives of this clade produced the antifungal polyketides of the sporothriolide type in standardized submerged cultures. Furthermore, a comparison of the morphology of this group of species formerly placed in Hypoxylon, including H. austrobahiense and H. rubigineoareolatum, also revealed certain morphological similarities. They are therefore accommodated in the new genus Hypomontagnella, with Hypomontagnella monticulosa as type species, and the new Argentine fungus is described as Hypomontagnella barbarensis.